Validação das escalas de preocupação com o peso corporal e de estresse percebido - Dias, Juliana Chioda Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objectives: perform a transcultural adaptation to Portuguese and validation of Weight Concerns Scale (WCS) and the Perceived Stress Scale (PSS), study the equivalence between the online and paper-and-pencil versions of WCS and verify the contribution of nutritional status, perceived stress and sociodemographic variables in concern with female university students’ weight. Methods: participated 1097 undergraduate female students enrolled in Pharmaceutical Sciences and Sciences and Linguistics schools at Universidade Estadual Paulista – UNESP campus of Araraquara (São Paulo) in 2011/2012. Were raised sociodemographic information and measurements such as weight and height. Performed translation and back-translation of instruments and then the validation procedures of face and content. Psychometric sensitivity of the items was evaluated using the summary measures (skewness and kurtosis). Conducted confirmatory factor analysis of the scales from the indices 2/gl (chi-square ratio for degrees of freedom), CFI (Confirmatory Fit Index), GFI (Goodness of Fit Index) and RMSEA (Root Mean Square Error of Approximation). To assess the stability of the models was performed a multi groups analysis. The invariance of the models was tested using the chi-square difference (Δ²) for the factor weights (), Covariance (Cov) and Residue (Res) of the models. Estimated the convergent validity of the measures from the Average Variance Extracted (AVE) and Composite Reliability (CR). The concurrent and divergent validity were calculated by correlation analysis (r) using the Body Shape Questionnaire (BSQ) and the student version of the Maslach Burnout Inventory (MBI). The internal consistency of the scales was calculated by standardized Cronbach’s alpha coefficient (α). For WCS was performed a study to adjust the application mode (online and paper-and-pencil) of the measuring instrument. The impact of variables in weight concerns was estimated by a ...

Objetivos: realizar a adaptação transcultural para o português e a validação da Weight Concerns Scale (Escala de Preocupação com o Peso – WCS) e da Perceived Stress Scale (Escala de Estresse Percebido – PSS), estudar a equivalência entre as versões online e em papel da WCS e verificar a contribuição do estado nutricional, estresse percebido e de variáveis sociodemográficas na preocupação com peso de estudantes universitárias. Métodos: participaram 1.097 estudantes do sexo feminino matriculadas nos cursos de graduação em Ciências Farmacêuticas e Ciências e Letras da Universidade Estadual Paulista – UNESP campus de Araraquara (SP) nos anos de 2011 e 2012. Foram levantadas informações sociodemográficas, além de medidas de peso e altura autorreferidos. Realizou-se a tradução e retrotradução dos instrumentos e, em seguida, os procedimentos de validação de face e de conteúdo. A sensibilidade psicométrica dos itens foi avaliada por meio das medidas de resumo (assimetria e curtose). Conduziu-se análise fatorial confirmatória das escalas utilizando os índices 2/gl (razão qui-quadrado e graus de liberdade), CFI (Confirmatory Fit Index), GFI (Goodness of Fit Index) e RMSEA (Root Mean Square Error of Approximation). Para avaliar a estabilidade dos modelos realizou-se análise multigrupos. A invariância entre os modelos foi testada utilizando-se a diferença do qui-quadrado (Δ²) para os pesos fatoriais (), para as Covariâncias (Cov) e Resíduos (Res) dos modelos. Estimou-se a validade convergente pelas medidas de Variância Extraída Média (VEM) e Confiabilibade Composta (CC). As validades concorrente e divergente foram calculadas por meio da análise correlacional (r) utilizando-se o Body Shape Questionnaire (BSQ) e a versão para estudantes do Inventário de Burnout de Maslach (MBI). A consistência interna das escalas foi calculada utilizando-se o Coeficiente alfa de Cronbach padronizado (α). Para ...
Keywords: Imagem corporal; Nutrição - Avaliação; Estudantes universitarias; Stress (Fisiologia); Nutrition Evaluation